Protecting Children in Migration: A Nexus between Migration and Child Protection in Ethiopia - International Organization for Migration (United Nations, 2025)
Ethiopia is a country of origin and transit, with migration primarily occurring around three main routes: (a) Eastern route through Djibouti towards Saudi Arabia; (b) Southern route through Kenya towards South Africa; and (c) Northern route through Libya towards Europe. In 2022, the number of unaccompanied children who migrated via the Eastern route doubled in comparison to 2021, and unaccompanied children made up 38 per cent of all children on the move from Ethiopia in 2022. En route, children may face protection risks including arbitrary arrest and detention, human trafficking for the purposes of labour or sexual exploitation, gender-based violence, extortion and denial of access to basic needs. Broad structural factors, such as conflict, drought and poverty are driving children and adults to migrate despite the protection risks. To understand the current knowledge gaps in the nexus between migration and child protection, as well as proposed improvements, this study relies on primary and secondary data analysis. With a particular focus on exploring linkages between child migration and trafficking in children in Ethiopia, the report concludes with the institutional and legal landscape for children on the move and highlights key policy gaps in protecting children on the move across Ethiopia.